EXISTENTIAL-PHILOSOPHICAL SYMBOLS AND MEANINGS IN THE SUFISTIC ROMAN “GHURBAH AL-GHARBIYAH” SUHRAWARDĪ: A HERMENEUTICAL STUDY - Lukman Hakim Rohim (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
Suhrawardī, as the founder of illumination philosophy, has works in the field of literature that have philosophical nuances. Researchers through this article attempt to examine philosophically-hermeneutically the Sufistic Romance of Ghurbah al-Gharbiyah Suhrawardī which has not been extensively studied by researchers including Suhrawardī scholars. The novel is genealogically related to Ḥay bin Yaqẓān by Ibn Sīnā and Ibn Ṭufayl, so it is called the Ḥay bin Yaqẓān trilogy: Avicenna, Ibnu Ṭufayl, and Suhrawardī. Through Ricoeur’s Hermeneutic Approach and Corbin’s Epistemology of Sufistic Imagination, which is used as a research method, researchers intend to interpret the symbols and existential meanings of Ghurbah al-Gharbiyah's novel. The purpose of this study is to interpret the background, symbols, and meaning behind Suhrawardī’s novel. The conclusion of this study: Ghurbah al-Gharbiyah discusses the philosophical theme of human alienation in the world with the use of symbols: the city of Qairawan as the imprisoned phase, the Hudhud bird as the enlightenment phase, and the journey on Mount Sinai during the liberation phase and meeting with the "Light of all Lights". Three phases each characterize today's Sufistic consciousness of man: the experience of alienation, enlightenment, and liberation. On the other hand, this novel is a representation of Suhrawardī's subjective creative imagination (al-quwwah al-khayāliyyah) inspired by prophetic experiences: Prophet Muhammad's Ascension, Prophet Sulaiman's Hudhud bird, and Prophet Musa's Mount Sinai.